RHYTHMIC TRANSKRANIAL MAGNETIC STIMULATION IN TREATMENT OF PATIENTS WITH DEPRESSION - Tretiakova, A. I.; Chebotariova, L. L.; Sulii, L. M.; Matrenytskiy, V. L. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
23 patients with clinically proven diagnosis of depression were treated with the help of rTMS. The signs of depression were assessed according to the Hospital Anxiety and Depression Scale (HADS) and Zung Self-Rating Depression Scale. The low-frequency (1 Hz) rTMS was conducted on “Neuro-MS/T” with the intensity of 80% from the threshold of motor response to the TMS of the right dorsolateral prefrontal cortex, number of trains – 60, duration – 23 minutes. After 10 sessions of rTMS, the patients noted the improvement of sleep (15), mood improvement (19), a calmer reaction to stressful situations (14). A reduction of depression severity according to assessment scales was also registered (р < 0,05). The therapeutic rTMS method and the chosen protocol of stimulation proved to be effective in treatment of depression and can be used in medical practice under the control of psychotherapist. 23 patients with clinically proven diagnosis of depression were treated with the help of rTMS. The signs of depression were assessed according to the Hospital Anxiety and Depression Scale (HADS) and Zung Self-Rating Depression Scale. The low-frequency (1 Hz) rTMS was conducted on “Neuro-MS/T” with the intensity of 80% from the threshold of motor response to the TMS of the right dorsolateral prefrontal cortex, number of trains – 60, duration – 23 minutes. After 10 sessions of rTMS, the patients noted the improvement of sleep (15), mood improvement (19), a calmer reaction to stressful situations (14). A reduction of depression severity according to assessment scales was also registered (р < 0,05). The therapeutic rTMS method and the chosen protocol of stimulation proved to be effective in treatment of depression and can be used in medical practice under the control of psychotherapist. 23 patients with clinically proven diagnosis of depression were treated with the help of rTMS. The signs of depression were assessed according to the Hospital Anxiety and Depression Scale (HADS) and Zung Self-Rating Depression Scale. The low-frequency (1 Hz) rTMS was conducted on “Neuro-MS/T” with the intensity of 80% from the threshold of motor response to the TMS of the right dorsolateral prefrontal cortex, number of trains – 60, duration – 23 minutes. After 10 sessions of rTMS, the patients noted the improvement of sleep (15), mood improvement (19), a calmer reaction to stressful situations (14). A reduction of depression severity according to assessment scales was also registered (р < 0,05). The therapeutic rTMS method and the chosen protocol of stimulation proved to be effective in treatment of depression and can be used in medical practice under the control of psychotherapist. 23 patients with clinically proven diagnosis of depression were treated with the help of rTMS. The signs of depression were assessed according to the Hospital Anxiety and Depression Scale (HADS) and Zung Self-Rating Depression Scale. The low-frequency (1 Hz) rTMS was conducted on “Neuro-MS/T” with the intensity of 80% from the threshold of motor response to the TMS of the right dorsolateral prefrontal cortex, number of trains – 60, duration – 23 minutes. After 10 sessions of rTMS, the patients noted the improvement of sleep (15), mood improvement (19), a calmer reaction to stressful situations (14). A reduction of depression severity according to assessment scales was also registered (р < 0,05). The therapeutic rTMS method and the chosen protocol of stimulation proved to be effective in treatment of depression and can be used in medical practice under the control of psychotherapist. 23 patients with clinically proven diagnosis of depression were treated with the help of rTMS. The signs of depression were assessed according to the Hospital Anxiety and Depression Scale (HADS) and Zung Self-Rating Depression Scale. The low-frequency (1 Hz) rTMS was conducted on “Neuro-MS/T” with the intensity of 80% from the threshold of motor response to the TMS of the right dorsolateral prefrontal cortex, number of trains – 60, duration – 23 minutes. After 10 sessions of rTMS, the patients noted the improvement of sleep (15), mood improvement (19), a calmer reaction to stressful situations (14). A reduction of depression severity according to assessment scales was also registered (р < 0,05). The therapeutic rTMS method and the chosen protocol of stimulation proved to be effective in treatment of depression and can be used in medical practice under the control of psychotherapist.